COMPARISON OF EFFICACY AND SAFETY OF PERIPHERAL IV-LINE MANNITOL VS HYPERTONIC SALINE FOR MANAGEMENT OF INTRACRANIAL PRESSURE - ASHRAF , H; ASHRAF , F; MALIK , S (Biological and Clinical Sciences Research Journal, 2024)
Management of elevated intracranial pressure (ICP) in emergency settings often involves the administration of hyperosmolar agents such as mannitol and hypertonic saline (HTS). The choice between these agents and their safety profile, mainly when administered via peripheral intravenous (IV) lines, remains a clinical concern. Objective: To compare the safety and effectiveness of peripheral IV administration of mannitol and hypertonic saline in managing elevated intracranial pressure in the emergency department. Methods: A retrospective cohort study was conducted in the Emergency Department of Shifa International Hospital from June 2023 to June 2024. The study included 200 adult and pediatric patients who received hyperosmolar agents, specifically 110 patients administered with a 1 g/kg bolus dose of 20% or 25% mannitol and 90 patients with a 5 mL/kg bolus dose of 3% hypertonic saline. The administration was followed by repeated doses or continuous infusion at the attending physician's discretion. The primary endpoint was the incidence of extravasation. In contrast, secondary endpoints included hypokalemia, acute kidney injury (AKI) within two days of admittance, hypernatremia, hyperchloremia, ICP at admission and 24 hours post-administration, length of hospital and ICU stay, need for ventilator support, mortality rate, Glasgow Coma Scale (GCS) score at discharge, and severity of infusion-related adverse effects. Results: The mannitol group consisted of older patients (52.8 ± 21.3 years vs. 28.6 ± 23.1 years), who were also heavier (75.2 ± 21.8 kg vs. 57.5 ± 33 kilograms), had a higher prevalence of end-stage renal disease (ESRD) (7.3%), and were less likely to present with altered mental status (89.1% vs. 97.8%). There were no incidents of extravasation in either group (p > 1). No significant differences were observed between the groups concerning secondary outcomes. However, the mannitol group exhibited higher ICP after 24 hours (4.240 ± 7.9 vs. 2.111 ± 6), a lower GCS score at discharge (3 [3-14] vs. 13 [3-15]), a higher mortality rate (55.5% vs. 33.4%), and a longer duration of ventilator support (2 days vs. one day). Conclusion: Peripheral IV administration of hypertonic saline appears safer and more effective in reducing intracranial pressure than mannitol in emergency department settings. HTS demonstrated a more favorable safety profile with lower mortality and shorter ventilator support duration.